Citra Perempuan Jawa Modern dalam Wacana Iklan di Media Massa - Mulyana, Mulyana (Jurnal Penerjemahan, 2021)
The purpose of this study is to describe and interpret the image of modern Javanese women as reflected in advertising discourse in the mass media. Depictions and interpretations are carried out to obtain the dominant characteristics or characteristics of modern Javanese women, especially from advertisements. The research was conducted with a qualitative descriptive design. Data were taken from print mass media (Djaka Lodang Magazine) and electronic (Retjo Buntung Radio, Pop FM). Data collection was carried out in the Yogyakarta area, over a period of 6 months (between Mey – October 2019), with incidental sampling. The results of the analysis of the research data show that; (1) advertising discourse is very influential in forming public impressions and opinions, (2) the image of modern Javanese women is depicted in five images, namely: good at managing the house, good at shopping, good at maintaining beauty, good at maintaining appearance, and good at taking care of the family. Keywords: women image, advertaising discourse, propotitional of discourse